Quality and Affordable Education through Quality Management Systems in Higher Education - Muhammad Afif Hasbullah; Nisaul Barokati Selirowangi; Mohammad Syaiful Pradana; Buyun Khulel; Moh Hudi (STAI Miftahul Ula Nganjuk, 2020)
The general goal of education is to develop Indonesian people completely in the sense that carried out education still maintain unity, diversity and develop individual’s ideals. Every citizen has the right to obtain education equally with excellence and a balance (equity) between the utilization (access) with achievement. The higher education system must be able to create a quality higher education that is also affordable by the people of Indonesia. A university leader must be in-line and lead a